Gamification of walking in nature : A field experiment with Pokémon GO Routes - Laato, Samuli; Rauti, Sampsa; Kordyaka, Bastian; Papangelis, Konstantinos; Jung, Sangwon; Nummenmaa, Timo; Hamari, Juho (Association for Computing Machinery (ACM), 2025)
There are numerous benefits from regularly walking in nature, and today's mobile technologies have the potential to encourage people to do so. Past research has showed that gamified map-based apps and location-based games (LBGs) have the capability to incentivize people to go to nature areas in cities and beyond. In this study, we explored LBGs' potential to bring people to nature by conducting a field experiment with a new mechanic called Routes in the popular LBG Pokémon GO. Prior to the Route feature's launch, we created altogether 13 Routes of various lengths in both city and nature landscapes. We collected numerical in-game data of how many times each Route was walked and deployed a survey (n=67) for Pokémon GO players in the area where the Routes were made. The findings suggest that proximity to population concentrations and in-game rewards are key drivers of Route popularity. Players' motivators to choose nature Routes over urban Routes were limited to outside-the-game factors such as scenery, and overall in our experiment the urban Routes turned out to be more popular.